Cell cultures of Maytenus ilicifolia Mart. are richer sources of quinone-methide triterpenoids than plant roots in natura - Coppede, Juliana S.; Pina, Edieidia S.; Paz, Tiago A. [UNESP]; Fachin, Ana L.; Marins, Mozart A.; Bertoni, Bianca W.; Franca, Suzelei C.; Pereira, Ana Maria S. (Springer, 2014)
The quinone-methide triterpenoids (QMTs) are chemotaxonomic markers of the family Celastraceae and many compounds of this class possess important anticancer and anti-inflammatory activities. However, the levels of QMTs in the roots of Celastraceous species are typically very low (ca. 0.0003 %) and commercial production by extraction from such tissues would not be commercially viable. With the aim of determining if cells cultured in vitro might provide alternative sources of these bioactive triterpenoids, we have quantified and compared the concentrations of QMTs accumulated by the roots of plants of Maytenus ilicifolia Mart. ex Reissek (Celastraceae) aged 0.5-10 years, and in callus and suspension cultures derived from a cell line that had been subcultured over a period of 10 years. Comparing plants cultivated in natura, the highest levels of QMTs were detected in the root bark of 5-year old specimens. However, cell suspensions derived from the long-term cell line retained their capacity to synthesize and accumulate QMTs, and presented levels of maytenin, 22 beta-hydroxymaytenin, celastrol and pristimerin that were, respectively, 1.96-, 2.48-, 8.85- and 3.29-times higher than those in the roots of 5-year old plants. The results presented herein open up new possibilities for the large-scale production of QMTs and for the development of novel pharmaceuticals.
Keywords: Maytenus ilicifolia; Cell suspensions; Maytenin; Celastrol; Pristimerin